Brahmara puṇi nabakalebara!! - Rath Śarmā, Sadāśiva, 1921- (Kaṭaka Shṭudenṭas Shṭora, 1977)
Philosophical interpretation of the rights of renewal of the image of Jagannatha, Hindu deity, enshrined at Puri.